Lobster Sales Prediction Using Adaptive Neuro Fuzzy Inference System (ANFIS) In Simeulue District - Sandira, Sri Delwis; Kurniawan, Rakhmat; Hasibuan, Muhammad Siddik (IJISTECH (International Journal of Information System and Technology), 2024)
The rapid progress of technology and information is making the challenges of the past become a tantalizing reality of the fourth industrial revolution. Rapid technological progress is marked by major developments in all aspects of life, such as economics, education, health, social and cultural. In the economic world, increasingly sophisticated technological developments will help the work of business actors and force them to innovate and be creative in improving the quality, capacity and products produced. With the vast lobster market, lobster demand experiences a sharp increase every year along with an increase in prices which will provide profits for fishermen in Simeulue. Therefore, predictions of lobster sales are quite important for fishermen in Semeulue to predict lobster sales that will be marketed abroad and domestically the following day, so that fishermen can estimate the lobster seeds or lobster catch needed optimally. In the prediction process The sales data obtained is in the form of a sales history report from 2017 to 2022, then the data obtained will be calculated using the adaptive neuro fuzzy inference system (ANFIS) to then obtain sales prediction results for the following year. And using MAPE calculations with the results of lobster sales training data calculations, the accuracy yields above 99% with a value of 0.0000168031. Therefore, this research will discuss predictions of lobster sales using the adaptive neuro fuzzy inference system (ANFIS) in Simeulue Regency.